CONCEPTUAL FOUNDATIONS OF IMPROVEMENT OF ECONOMIC REGULATION OF RATIONAL NATURAL RESOURCES USE IN MARKET CONDITIONS - Pozdnyakov, Andrey Leonidovich (Journal of Applied Engineering Science, 2018)
The article is devoted to options for the economic regulation of environmental pollution. Possible types of damage caused to the environment, the concept of "external damage", its value are analyzed. Some principles are outlined for the development of an effective concept of the economic mechanism of nature management. It is noted that it is in the sphere of urban planning that an effective implementation of the economic mechanism of nature management is possible due to the territorial complexity of this type of activity. Reproduction of the environment as an integral part of the productive forces of society is a necessary condition for the continuity of the process of social reproduction. The study of the economic efficiency of environmental protection, both in the theoretical aspect and for management practice, involves solving complex problems of methodology and classification, as well as the development of appropriate methods and tools.
Keywords: reproduction; manager; economizer